Engineering Seismology, Geotechnical and Structural Earthquake Engineering - D'Amico, Sebastiano (IntechOpen, 2013)
The mitigation of earthquake-related hazards represents a key role in the modern society. The mitigation of such kind of hazards spans from detailed studies on seismicity, evaluation of site effects, and seismo-induced landslides, tsunamis as well as and the design and analysis of structures to resist such actions. The study of earthquakes ties together science, technology and expertise in infrastructure and engineering in an effort to minimize human and material losses when they inevitably occur. Chapters deal with different topics aiming to mitigate geo-hazards such as: Seismic hazard analysis, Ground investigation for seismic design, Seismic design, assessment and remediation, Earthquake site response analysis and soil-structure interaction analysis.